An update: improvements in imaging perfluorocarbon-mounted plant leaves with implications for studies of plant pathology, physiology, development and cell biology - Littlejohn, George R.; Mansfield, Jessica C.; Christmas, Jacqueline T.; Witterick, Eleanor; Fricker, Mark D.; Grant, Murray R.; Smirnoff, Nicholas; Everson, Richard M.; Moger, Julian; Love, John (Frontiers in Plant Science, 2014)
Plant leaves are optically complex, which makes them difficult to image by light microscopy. Careful sample preparation is therefore required to enable researchers to maximise the information gained from advances in fluorescent protein labelling, cell dyes and innovations in microscope technologies and techniques. We have previously shown that mounting leaves in the non-toxic, non-fluorescent perfluorocarbon (PFC), perfluorodecalin (PFD) enhances the optical properties of the leaf with minimal impact on physiology. Here, we assess the use of the perfluorocarbons PFD, and perfluoroperhydrophenanthrene (PP11) for in vivo plant leaf imaging using 4 advanced modes of microscopy: laser scanning confocal microscopy (LSCM), Two-photon fluorescence (TPF) microscopy, second harmonic generation (SHG) microscopy and stimulated Raman scattering (SRS) microscopy. For every mode of imaging tested, we observed an improved signal when leaves were mounted in PFD or in PP11, compared to mounting the samples in water. Using an image analysis technique based on autocorrelation to quantitatively assess LSCM image deterioration with depth, we show that PP11 outperformed PFD as a mounting medium by enabling the acquisition of clearer images deeper into the tissue. In addition, we show that SRS microscopy can be used to image perfluorocarbons directly in the mesophyll and thereby easily delimit the “negative space” within a leaf, which may have important implications for studies of leaf development. Direct comparison of on and off resonance SRS micrographs show that PFCs do not to form intracellular aggregates in live plants. We conclude that the application of PFCs as mounting media substantially increases advanced microscopy image quality of living mesophyll and leaf vascular bundle cells.